Convexidades de caminhos e convexidades geométricas - Araújo, Rafael Teixeira de (2014)
In this dissertation we present complexity results related to the hull number and the convexity number for P3 convexity. We show that the hull number and the convexity number are NP-hard even for bipartite graphs. Inspired by our research in convexity based on paths, we introduce a new convexity, where we defined as convexity of induced paths of order three or P∗ 3 . We show a relation between the geodetic convexity and the P∗ 3 convexity when the graph is a join of a Km with a non-complete graph. We did research in geometric convexity and from that we characterized graph classes under some convexities such as the star florest in P3 convexity, chordal cographs in P∗ 3 convexity, and the florests in TP convexity. We also demonstrated convexities that are geometric only in specific graph classes such as cographs in P4+-free convexity, F free graphs in F-free convexity and others. Finally, we demonstrated some results of geodesic convexity and P∗ 3 in graphs with few P4’s.